Bill Viola’s Mysticism: Art and Spirituality - Daelemans, Bert (Razón y fe, 2020)
Recently, the Episcopal Museum of Vic exhibited the artwork Visitation, by Bill Viola, offering the opportunity to reflect on the role that art plays in making present the dimension of transcendence in our society. Here we highlight ten characteristics of his “mysticism”, which Viola finds at the limits of existence, as when he has to face the death of his parents. Without answering directly, he sharpens the question of life beyond, intensifying the idea of the threshold. In this sense, every work of art should be an “annunciation” of the spiritual background of life, which does not remove it from the ordinary, but allows it to be celebrated more intensely.
Keywords: contemporary art; spirituality; Bill Viola; transcendence; video art; life and death; secularization